The Psychosocial Role of Body Image in the Quality of Life of Head and Neck Cancer Patients. What Does the Future Hold?—A Review of the Literature - Vlad Ioan Covrig; Diana Elena Lazăr; Victor Vlad Costan; Roxana Postolică; Beatrice Gabriela Ioan (Medicina, 2021)
Background and Objectives: It is well known that among all cancers, cancers of the head and neck (HNC) have a major impact on patients’ quality of life. Disfigurement, anxiety and disabling physical and psychological symptoms affect people with HNC to such an extent that the suicide rate in this category of patients is exceeded only by that of patients with pancreatic cancer. The aim of this review was to summarize the published literature describing the severity of body image and quality of life impairment in patients with HNC over time, and to examine the psychosocial and functional associations and interventions implemented to improve body image and quality of life. Materials and Methods: We conducted a literature search from 1 January 2018 to June 2021 that included electronic searches of six major databases (PubMed, ScienceDirect, ProQuest, PsycINFO, PsychArticles and Scopus) and review of references of articles screened. Of 620 records, only 9 articles met the eligibility criteria. Results: Numerous studies have been conducted to analyze various psychological variables, but there is still a lack of standardization in the assessment of body image perception (BI) and quality of life, resulting in small-scale testing of interventions with poor results. Conclusions: Expected longitudinal studies describing the flow of body image problems and the mediation and balance factors associated with body image will allow researchers to design methods aimed at limiting body image disorders and thus improving quality of life of patients with head and neck cancer.